Jesus as teacher in the Gospel of Mark: the function of a motif - Hershman, Evan (T & T Clark Ltd, 2020)
"Evan Hershman seeks to examine Mark's portrayal of Jesus as teacher in comparison with portrayals of teachers in contemporary Greco-Roman literature, and argues that the teaching motif in Mark is used in highly distinctive ways. He argues that careful study reveals Mark's use of the trope does not aim to expound a fully fleshed-out ethical agenda, but rather to emphasize Jesus's unique authority, incorporate conflicts with other claimants to authority into the Gospel narrative, and persuade the gospel audience to accept his Christological vision and its demands on their lives. Hershman develops these three related themes behind the motif of moral instruction, and offers suggestions for how this portrayal of Jesus fits with the historical and social context in which the Gospel was written. By analyzing not only teaching and authority throughout Mark, but also numerous Greek and Greco-Roman texts concerning teachers and learning, Hershman creates a new reading of significant Markan passages - such as the parables discourse and the temple incident - in light of a focus on the importance of Jesus's teachings to the plot of the Gospel."--